Adaptabilitas Agronomi Genotipe Kacang Merah di Dataran Rendah Bogor - Marwiyah, Siti; Undang, Undang; Agustiani, Soefi Nastri (Vegetalika, 2025)
Evaluation of kidney bean genotypes in the lowlands is a preliminary step in a plant breeding program to develop lowland-adaptive varieties. This study aims (1) to evaluate agronomic characters, (2) analyze the associations between yield component traits and total yield, and (3) select kidney bean genotypes adapted to lowland environment. The study was conducted in lowlands (185 m asl), Leuwikopo Experimental Station, IPB, Bogor, from March to June 2023. Ten kidney bean genotypes were arranged in a randomized complete block design. Observations included growth characters and yield components, followed by heritability, correlations, and multiple regression. Genotype was significantly affects plant height, total productive bunches, total pods number, total pod weight, total seed weight, and pod length. Characters with high broad sense heritability (h2bs>60%) were plant height, total productive bunches, pod length, total pod weight, and total seed weight. Total seed weight was identified as a selection trait for adaptation in lowland. Adaptive genotypes in the lowlands exhibited high total pod and seed weight, taller canopy, numerous productive clusters, and early maturity. Genotypes KM06, KM03, and KM04 showed the highest total seed weight per plant, indicating superior adaptation potential in lowland environments.